Ocular Fundus Photography as a Tool to Study Stroke and Dementia - Cheung, Carol Y.; Chen, Christopher; Wong, Tien Y. (Seminars in Neurology, 2015)
Although cerebral small vessel disease has been linked to stroke and dementia, due to limitations of current neuroimaging technology, direct in vivo visualization of changes in the cerebral small vessels (e.g., cerebral arteriolar narrowing, tortuous microvessels, blood–brain barrier damage, capillary microaneurysms) is difficult to achieve. As the retina and the brain share similar embryological origin, anatomical features, and physiologic properties with the cerebral small vessels, the retinal vessels offer a unique and easily accessible “window” to study the correlates and consequences of cerebral small vessel diseases in vivo. The retinal microvasculature can be visualized, quantified and monitored noninvasively using ocular fundus photography. Recent clinic- and population-based studies have demonstrated a close link between retinal vascular changes seen on fundus photography and stroke and dementia, suggesting that ocular fundus photography may provide insights to the contribution of microvascular disease to stroke and dementia. In this review, we summarize current knowledge on retinal vascular changes, such as retinopathy and changes in retinal vascular measures with stroke and dementia as well as subclinical makers of cerebral small vessel disease, and discuss the possible clinical implications of these findings in neurology. Studying pathologic changes of retinal blood vessels may be useful for understanding the etiology of various cerebrovascular conditions; hence, ocular fundus photography can be potentially translated into clinical practice.
Keywords: retina; ocular fundus photography; retinal vascular changes; stroke; dementia; small vessel diseases